Pengaruh Perlakuan Steam pada Strand dan Shelling Ratio terhadap Sifat Fisis dan Mekanis Oriented Strand Board Bambu (Effect of Steam Treatment on Strand and Shelling Ratio on the Physical and Mechanical Properties of Bamboo Oriented Strand Board) - Sena Maulana; Byantara D Purusatama; Nyoman J Wistara; Ihak Sumardi; Fauzi Febrianto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2016)
The objective of this study was to evaluate the physical and mechanical properties of bamboo oriented strand board (OSB) from andong (Gigantochloa pseudoarundinacea) with steam treatment on strand at various shelling ratios. Strands were steam-treated at 126 ºC for 1 h under 0.14 MPa pressure. Three-layer OBSB with the core layer perpendicular to the surface at various shelling ratio (15/70/15, 20/60/20, 25/50/25, 30/40/30) was formed and bonded with 8% of phenol formaldehyde resin. Wax was added amount of 1% based on oven dry strand. The evaluation of physical and mechanical properties of the boards was conducted in accordance to the JIS A 5908:2003 standard. Steam treatment tended to increase the dimensional stability and mechanical properties of OBSB from andong. The higher shelling ratio increased the parallel flexural properties, but decreased the perpendicular flexural properties.